Anxiety mediates the relationship between multidimensional perfectionism and insomnia disorder. (January 2017) - Akram, Umair; Ellis, Jason G.; Myachykov, Andriy; Chapman, Ashley J.; Barclay, Nicola L.
Abstract: Individuals with insomnia often report aspects of perfectionism alongside symptoms of anxiety and depression. However, there has been limited examination of these factors together. The current study investigated whether individuals with insomnia report increased perfectionism compared to normal-sleepers. Further, the mediating role of anxiety and depression was examined. Participants were 39 individuals with DSM-5 defined Insomnia Disorder, and 39 normal-sleepers, who completed two measures of multidimensional perfectionism and the Hospital Anxiety and Depression Scale. Results demonstrated that, compared to normal-sleepers, individuals with insomnia display increased perfectionistic traits of: concern over mistakes, doubts about action, and parental criticism. In addition, these differences were partiality mediated by symptoms of anxiety, but not depression. Our findings highlight the significance of treating symptoms of anxiety with the prospect of alleviating negative thoughts concerning one's mistakes, doubts about action, and perception of parental criticism, which may contribute to insomnia. Highlights: Individuals with insomnia report greater aspects of perfectionism. This relationship appears to be mediated by anxiety symptoms. Anxiety treatment may alleviate perfectionistic standards in the context of sleep.